Effect of Common Buffers and Heterocyclic Ligands on the Binding of Cu(II) at the Multimetal Binding Site in Human Serum Albumin. (5th May 2010) - Sokołowska, Magdalena; Pawlas, Krystyna; Bal, Wojciech
Abstract : Visible-range circular dichroism titrations were used to study Cu(II) binding properties of Multimetal Binding Site (MBS) of Human Serum Albumin (HSA). The formation of ternary MBS-Cu(II)-Buffer complexes at pH 7.4 was positively verified for sodium phosphate, Tris, and Hepes, the three most common biochemical buffers. The phosphate > Hepes > Tris order of affinities, together with strong spectral changes induced specifically by Tris, indicates the presence of both Buffer-Cu(II) and Buffer-HSA interactions. All complexes are strong enough to yield a nearly 100% ternary complex formation in 0.5 mM HSA dissolved in 100 mM solutions of respective buffers. The effects of warfarin and ibuprofen, specific ligands of hydrophobic pockets I and II in HSA on the Cu(II) binding to MBS were also investigated. The effects of ibuprofen were negligible, but warfarin diminished the MBS affinity for Cu(II) by a factor of 20, as a result of indirect conformational effects. These results indicate that metal binding properties of MBS can be modulated directly and indirectly by small molecules.